STUDENTS’ VIRTUAL DRAMA PERFORMANCE OF ENGLISH LANGUAGE TEACHING IN THE DIGITAL ERA: CREATIVITY AND ADAPTATION IN LEARNING - Inderawati, Rita; Meyers, Karen Ferreira; Novarita, Novarita; Awalludin, Awalludin; Anam, Syamsul (English Review: Journal of English Education, 2024)
Abstract: The COVID-19 pandemic has necessitated rapid adaptation to digital and remote learning, fundamentally altering traditional pedagogical practices. For English Education students, especially those engaged in literature courses, drama performance has long been a valuable tool for exploring and expressing literary understanding. However, the sudden shift to online learning environments presented unique challenges, pushing students to reconceptualize drama performance in a virtual setting. This study investigates how English Education students creatively adapted to these changes by producing virtual drama performances through the Zoom platform. The integration of virtual backgrounds, designed using Canva, allowed students to construct imaginative settings that supported narrative immersion, despite the physical separation. This research highlights the ways students utilized digital tools to convey dramatic elements and literary interpretation, transforming conventional stagecraft into an innovative, digital form of storytelling. Through in-depth analysis, this article explores how these virtual performances not only maintained the integrity of drama as a medium for literary education but also fostered critical technological skills that are increasingly relevant in the digital era. The findings demonstrate that virtual drama projects encouraged students to combine creativity with technical proficiency, enhancing their adaptability, digital literacy, and ability to collaborate in a remote context. This study underscores the evolving role of literature-based performance in English Language Teaching (ELT), suggesting that the integration of digital tools in creative projects may serve as a sustainable model for literature education in the post-pandemic future.